A NEW HOST RECORD AND NEW SPECIES OF THE GENUS BRUEELIA KÉLER, 1936 (PHTHIRAPTERA: ISCHNOCERA: PHILOPTERIDAE) FROM ZEBRA FINCH (PASSERIFORMES: ESTRILDIDAE) FROM SINDH, PAKISTAN - Saima Naz; Syed Anser Rizvi (Journal of Animal and Plant Sciences, 2018)
The Zebra finch, Taeniopygia guttata (Passeriformes: Estrildidae) is a captive bird in Sindh. They were observed for their chewing lice in captivity from different regions of Sindh. About 41 specimens of genus Brueelia Kéler (Phthiraptera: Ischnocera: Philopteridae) were collected from sixteen birds; mounted permanently in Canada balsam using standard methods. The specimens were compared with the different species of genus Brueelia, reported from other estrildid birds of the world. Differences were noticed in head sutures, chaetotaxy, male and female terminalia, subgenital plates and male genitalia, also in their body sclerotization, pigmentation and morphometry. On the basis of these taxonomic characters, the new species Brueelia spinosum sp.n.is proposed. This is the first report of a chewing louse from the zebra finch in the world.
Keywords: Brueelia; new species; new record; zebra finch; Sindh; Pakistan